Consumer choice and protection [videorecording] - Breitenmoser, Kurt; Dent, Louisa; Video Education Australasia ([Bendigo, Vic.] : Video Education Australasia, 2010)
This Australian-made, curriculum fit program examines the lures and pitfalls of shopping. We talk to an expert on consumer choice and offer some tips and tricks to improve your financial literacy, helping you to shop as a clever consumer
Executive producer, Simon Garner ; script editor, Ally Chumley
Voice over : Debbie Arpini
Subtitle available in English
Keywords: Consumer education; Shopping; Consumer protection